Inoculation efficiency of Azospirillum brasilense on economising nitrogen fertiliser in landrace popcorn - Martins, Tainara (2018)
Nitrogen is one of the nutrients most demandedby popcorn, and one that most increases production costs. Considering these factors, the aim of this study was to evaluate the effectiveness of inoculatingpopcorn seeds with Azospirillum brasilense together with four levels of nitrogen fertiliser, and its contribution to characteristics related to production. The experiment was carried out in the experimental area of the Centre for Agrarian Sciences and Biodiversity of the Federal University of Cariri, in Crato, in the State of Ceará. Eight treatments were evaluated with four replications, using an experimental design of randomised blocks in a 2x4 factorial scheme corresponding to the presence and absence of inoculation, and to four doses of nitrogen as top dressing. The following characteristics were evaluated: plant height, height of ear insertion, number of plants, number of lodged plants, number of broken plants, number of poorly husked ears, ear diameter, ear length, number of ears, number of diseased ears, number of infested ears, grain productivity, ear weight, mean 100-grain weight, and expansion capacity. There were significant differences for most of the characteristics under evaluation, with an increase of 17.18% in the number of ears and 10.78% in grain productivity, reducing the top dressing to 50 kg ha-1 in the presence of A. brasiliensi. These results demonstrate the potential for economisingnitrogen fertiliser in popcorn production under the soil and climate conditions of the Cariri region of the State of Ceará.